Effective adsorption of Congo red by a MOF-based magnetic material. Issue 14 (20th March 2019) - Han, Li-Juan; Ge, Fa-Yuan; Sun, Guo-Hao; Gao, Xiang-Jing; Zheng, He-Gen
Abstract : A highly water-stable MOF-based magnetic material Fe3 O4 @ZTB-1 has been obtained, and it exhibited an excellent adsorption capacity for Congo red. The electrostatic interactions and hydrogen bond are responsible for binding of CR with Fe3 O4 @ZTB-1. Abstract : Metal–organic frameworks (MOFs) are an exciting class of porous crystallized materials, which have attracted great interest in sustainable energy and environmental remediation. Magnetite (Fe3 O4 ) is one of the best-known magnetic materials and has been extensively studied with respect to properties involving high saturation magnetization, biocompatibility and low toxicity. The combination of MOFs and Fe3 O4 has shown its potential applications in drug delivery, catalysis and wastewater treatment. However, only classical porous MOFs are used to encapsulate magnetic nanoparticles, such as MIL-100(Fe), ZIF-8, UiO-66 and so on. Herein, we firstly synthesized a new MOF ZTB-1 and surveyed its applications in magnetic materials. As a result, a highly water-stable MOF-based magnetic material Fe3 O4 @ZTB-1 has been obtained, and it was for the first time used as an excellent adsorbent for the fast adsorption of Congo red (CR) from aqueous solutions, exhibiting an adsorption capacity of 458 mg CR per gram. The electrostatic interactions and hydrogen bond are responsible for binding of CR with Fe3 O4 @ZTB-1. The magnetic material Fe3 O4 @ZTB-1 shows a potential application in dyeing wastewater treatment.